Combined effects of fuel reactivity, φ-sensitivity, and intake temperature on the performance of low-temperature gasoline/polyoxymethylene dimethyl ethers combustion. (15th March 2021) - Duan, Huiquan; Jia, Ming; Bai, Jinpeng; Li, Yaopeng
Highlights: The impacts of PODEn on LTGC were comprehensively investigated. The dominant factors for LTGC operated under different modes were identified. The higher reactivity of P20G80 dominates fuel stratification combustion mode. Gasoline/PODEn RCCI demonstrates the best performance. Abstract: This study focuses on investigating the combined effects of fuel reactivity, equivalence ratio ( φ )-sensitivity, and intake temperature ( T in ) on the performance of low-temperature gasoline combustion. To achieve this goal, the combustion characteristics of pure gasoline and gasoline/polyoxymethylene dimethyl ethers (PODEn ) blend with the volume fraction of 80%/20% (P20G80) were first investigated under premixed and fuel stratification operations. It is found that compared with pure gasoline, the required lower T in of P20G80 plays a greater role than its higher reactivity under premixed operation, and thereby results in lower combustion rate and nitrogen oxides (NOx ) emissions. However, the lower T in simultaneously yields decreased combustion efficiency. Unlike premixed operation, the higher reactivity of P20G80 dominates the combustion process of fuel stratification operation, contributing to shorter burn duration. However, the faster combustion rate does not significantly raise the combustion temperature of P20G80 in stratification operation. Then, the performance of dual-fuel reactivity-controlled combustion ignition (RCCI) fueled with gasoline/P20G80 and gasoline/PODEn was investigated. For gasoline/P20G80 RCCI, although the higher φ -sensitivity of P20G80 allows more advanced 50% burn point (CA50) without the occurrence of knock, the increased heat transfer losses yield lower engine efficiency than gasoline stratification operation. Only gasoline/PODEn RCCI takes full advantage of the higher φ -sensitivity and the lower required T in of PODEn, allowing more advanced CA50 to increase the expansion work, as well as weaker stratification to avoid the formation of local over-rich regions. Therefore, gasoline/PODEn RCCI presents the highest efficiency while keeping the NOx and soot emissions far below the Euro VI limit.